A global scoping review of adaptations in nurturing care interventions during the COVID-19 pandemic - Godoi, Lidia; Schenkman, Simone; Baumann, Ana A.; Bousquat, Aylene; Buccini, Gabriela (Frontiers in Public Health, 2024)
Background During the COVID-19 pandemic, children faced a disproportionate burden of malnutrition and poor health outcomes. Nurturing care interventions (NCIs) including actions toward good health, adequate nutrition, responsive care, opportunities for early learning, and security and safety are critical for promoting equity. Due to the need for evidence-based responses and preparedness, we analyzed adaptations in NCIs’ implementation strategies during COVID-19 according to the Framework for Reporting Adaptations and Modifications to Evidence-based Implementation Strategies (FRAME-IS). Method We conducted a global scoping review including peer-reviewed and non-peer-reviewed literature. The databases searched were PubMed, Embase, Scopus, BVS, Scielo, and Web of Science. This search was complemented by an extensive examination of relevant websites and an additional internet search via Google Scholar. We extracted and analyzed the data following the seven modules of the FRAME-IS. Results Out of 20 records, 27 NCI were identified across Africa (n = 3), Asia (n = 7), Europe (n = 3), North America (n = 11), Oceania (n = 1), and South America (n = 2). NCIs adapted their content (e.g., adding elements), evaluation (e.g., conducting needs assessment), training (e.g., using experts), and context (e.g., setting—shifting from in-person to remote, and population—expanding interventions’ reach). Adaptation goals were to increase acceptability (n = 9, 32.1%), adoption (n = 5, 17.8%), appropriateness (n = 10, 35.7%), feasibility (n = 25, 89.3%), penetration (n = 15, 53.6%), sustainability (n = 23, 82.1%), and fidelity (n = 1, 3.7%). The rationale to adapt varied from sociopolitical (n = 6, 21.4%), organizational (n = 13, 46.4%), implementer (n = 11, 39.3%), practitioner (n = 15, 53.6%), and recipient (n = 11, 39.3%). A quarter were reactive planned adaptations and 75.0% were unplanned modifications. Decisions were led by program leaders (n = 21, 75.0%), funders (n = 9, 32.1%), partners (n = 3, 10.7%), researchers (n = 1, 3.6%), and practitioners (n = 3, 10.7%). Adaptations were widespread from unit (e.g., hospital) (n = 1, 3.6%), organization (n = 4, 14.3%), and community system (e.g., countrywide) (n = 14, 50.0%). Conclusion The results from our global scoping review show that it is possible for NCIs to continue and even improve their delivery despite the global crisis, suggesting that remote delivery is feasible and can work as an alternative when in lockdown. Strategic planning taking advantage of existing structures and partnerships may have allowed NCI adaptations to be sustainable as well as facilitated replication within the organization network system.